The Blue, the Green, and the Toxic: Knowledge, Attitudes, and Practices of Physicians and Veterinarians Regarding Harmful Algal Blooms - Moser, Karin (My University, 2012)
Worldwide, 60% of cyanobacteria, or blue-green algae samples contain harmful toxins that could lead to adverse health effects in both humans and animals. When these bacteria proliferate they are known as Harmful Algal Blooms (HABs). Between June 1and October 1, 2011, there were 13 human and 7 animal cases of HAB-related illnesses in the state of Kansas. Since the inception of the Harmful Algal Bloom monitoring program in 2010, the Kansas Department of Health and Environment (KDHE) has worked to improve various aspects of the program. One aspect of the program which was identified as needing improvement was the reporting of human and animal illnesses related to HABs. A knowledge, attitudes and practices survey was created and sent electronically and through the mail to a random sample of Kansas licensed physicians and veterinarians (700 physicians, 796 veterinarians) to determine the success of the public health messaging campaign performed by KDHE to increase reporting of HAB-related illnesses. It was determined that while diagnosis of HAB-related illness increased from the summer of 2010 to the summer of 2011, the reported awareness before and after the messaging campaign did not change significantly among these health care professionals. Therefore, it was concluded that increased efforts (such as television news broadcasts, social networking, and radio station broadcasts) could be made by KDHE to educate physicians, veterinarians and the general public about where and when HAB- related illness can be reported to KDHE.
Keywords: Harmful algal bloom; Blue-green algae; Cyanobacteria; Public health; Public Health (0573)